Isolated Coarctation of the Aorta: Current Concepts and Perspectives - Bhatt, Ami B.; Lantin-Hermoso, Maria R.; Daniels, Curt J.; Jaquiss, Robert; Landis, Benjamin John; Marino, Bradley S.; Rathod, Rahul H.; Vincent, Robert N.; Keller, Bradley B.; Villafane, Juan (Frontiers in Cardiovascular Medicine, 2022)
Current management of isolated CoA, localized narrowing of the aortic arch in the absence of other congenital heart disease, is a success story with improved prenatal diagnosis, high survival and improved understanding of long-term complication. Isolated CoA has heterogenous presentations, complex etiologic mechanisms, and progressive pathophysiologic changes that influence outcome. End-to-end or extended end-to-end anastomosis are the favored surgical approaches for isolated CoA in infants and transcatheter intervention for children and adults. Primary stent placement is the procedure of choice in larger children and adults. Most adults with treated isolated CoA thrive, have normal daily activities, and undergo successful childbirth. Fetal echocardiography is the cornerstone of prenatal counseling and genetic testing is recommended. Advanced 3D imaging identifies aortic complications and myocardial dysfunction and guides individualized therapies including re-intervention. Adult CHD program enrollment is recommended. Longer follow-up data are needed to determine the frequency and severity of aneurysm formation, myocardial dysfunction, and whether childhood lifestyle modifications reduce late-onset complications.